Perrault’s tales illustrated by doré and the game of differences - Chagrot , Ghislaine; Moog, Pierre-Emmanuel (Ondina - Ondine, 2020)
Gustave Doré’s very detailed illustrations of Perrault’s fairy tales offer the opportunity to easily pinpoint differences between text and image. This operation allows us to better understand both the text and what is at stake in the illustrations. It consists of three steps. First must be identified the text corresponding to the image, then the main differences between them, and finally the impact of those differences on the meaning of the story. With three examples of illustrations by Doré, we will assess the extent to which the nonconformity of images to the text entails a positive or negative change in the meaning of the text. This educational use of the album for a better understanding of the narrative is not only recreational, it also gives a heuristic value to errors and anomalies. Keywords: Perrault’s Fairy Tales, Gustave Doré, Fairy tales and illustrations, Fairy tale and school use, Little Red Riding Hood